If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + 14 = 7 + -1(-2y) Reorder the terms: 14 + -5y = 7 + -1(-2y) Remove parenthesis around (-2y) 14 + -5y = 7 + -1 * -2y Multiply -1 * -2 14 + -5y = 7 + 2y Solving 14 + -5y = 7 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 14 + -5y + -2y = 7 + 2y + -2y Combine like terms: -5y + -2y = -7y 14 + -7y = 7 + 2y + -2y Combine like terms: 2y + -2y = 0 14 + -7y = 7 + 0 14 + -7y = 7 Add '-14' to each side of the equation. 14 + -14 + -7y = 7 + -14 Combine like terms: 14 + -14 = 0 0 + -7y = 7 + -14 -7y = 7 + -14 Combine like terms: 7 + -14 = -7 -7y = -7 Divide each side by '-7'. y = 1 Simplifying y = 1
| 2x+5=7x+3-x | | 2z=2(x-3) | | 21(x-84)=42 | | x-7.8=-6.2 | | 7x+9=9+7x | | h-15=-22 | | 23*67+93x=33 | | 2x-2x=3 | | 25x-3=45x+9 | | x^2+10X-700=0 | | 2x^2+24-19x=0 | | x^2+10X-700=o | | -(x+6)=10 | | 168.2=x^2*20 | | (8w+5)=21 | | 416/52*130/24= | | (N-3)=5 | | -7(2b+2)+(15b-8)=0 | | 1/2+3/2=9/2-1/2 | | ((4x)+(3x+12))+112=180 | | 9b+8=80 | | 7b-9=208 | | 3t-8=-104 | | 3y-8=88 | | 7y-11+4y+6=0 | | 2x+11=2x-11 | | 2x^2+19=12x | | 0.3r+0.2=1.7 | | x^2-11=110 | | 9x+6=174 | | 15(t-2)+3t=6(3t+4)-10 | | 4(x-1)+27=4x+23 |